Trabalhadores de saúde (1900-1920): contribuição para a sua história - Lima, Julio Cesar França (1994)
The world is now undergoing important changes in its technological foundations due to the Third Industrial Revolution. The period is characterized by a growing destruction of work positions and by the certainty that some occupations will disappear, although it is still not certain which occupations, in which sectors and with what speed this will occur. Paradoxically, the flexibility of new technologies has been demanding educational flexibility, as well as improvements in the standard of formal education ofthe population. Historically, the technologies socially produced by mankind, both in its material and immaterial forms, have not only destroyed working positions, but also disregarded the school system due to the imperatives of capital valorization. This is what the present study shows, by means of na analysis of technological application ofthe knowledge socially produced in the 'microbe age'. Determined by these relations, this knowledge determines new sanitary practices, besides the shift of the desinfection workers as a professional category, with the creation of a new speciality for a recent professional category: the professional nurse. Supported by the Taylorist paradigm, a ''modem formula' created by capital to objectifY it, manual work is reduced to a task in the process of mechanization ofmankind itself. Bearing in mind these historical references and the assumption that production of knowledge originates from social work relations and social production relations, it is important to stress the challenge of evaluating the construction' of a new foundation for worker qualification, in a society that still carries the tamt of a proslavery culture.These foundations, guided by the word of me~ point towards a comprehensive education for workers rather than the professional reductionism of the Human Capital theory.